Elaboration, characterization and magnetic properties of cobalt nanoparticles synthesized by ultrasonic spray pyrolysis followed by hydrogen reduction. (February 2017) - Shatrova, Nadezda; Yudin, Andrey; Levina, Vera; Dzidziguri, Ella; Kuznetsov, Denis; Perov, Nikolay; Issi, Jean-Paul
Graphical abstract: Highlights: A two-step synthesis technique of nanostructured cobalt microspheres is proposed. The dependence on synthesis conditions of the microspheres properties is evidenced. The second step (reduction) has a direct impact on the magnetic coercive force. Abstract: Nanostructured cobalt microspheres were synthesized by a two-stage method. First, cobalt oxide Co3 O4 nanostructured microspheres were synthesized by spray pyrolysis at 700, 800, 900, 1000, and 1100, °C. Second, the nanostructured powders thus obtained were reduced to metal cobalt in a hydrogen atmosphere at 300 °C. For a sample obtained at 1000 °C, the influence of the reduction temperatures (220, 240, 270, 300, and 350 °C) on the metal cobalt powders properties was investigated. All the samples obtained were characterized by means of X-ray diffraction (XRD), coherent length determination and scanning electron microscopy (SEM). In addition, an average size of the particles, a specific surface area, and an effective diameter were determined. Finally, the magnetic properties of the metal cobalt, such as coercive force, saturation, and residual magnetization were measured by vibration sample magnetometer (VSM). The dependence on synthesis conditions of nanostructured metal cobalt microspheres properties was highlighted.